iTRASH plastic compactor: innovative rubbish container / Farrah Noor Ahmad ... [et al.] - Noor Ahmad, Farrah; Mohd Asri, Muhammad Haziq; Ahmad, Muhammad Adi Ikhwan; Rahimi Rosli, Muhammad Rafiq; Zakaria, Sazarul Aiman (Universiti Teknologi MARA, Perak, 2020)
A trash container is intended for a temporary waste storage in a designated area prior to its disposal of which recycling is not emphasized and taken into consideration. The objective of this project is to design an innovative trash container that will be able to increase efficiency of recycling based on plastic bottles, which is more feasible for all. It involves the compression mechanism which transformed the plastic bottles into smaller than its original sizes. This will provide some space to keep the disposed bottles before being sent to the recycling centre. The concept of this project is translated through calculation, simulations, and even customizing a digital prototype of trash container. CATIA software performs the simulation on the critical component known as gear, which suggests promising results without higher stress that could possibly damage the gear. As a result, the rendering waste shall be compressed more efficiently. Manual control of the element compaction from the handle to the piston via gears demonstrates the product’s uniqueness making it more fun, simple and easy to operate. This will pave the way to encourage users to be highly involved in the recycling process and lead to the sustainable waste management approach.